Tailored glycosylated anode surfaces: Addressing the exoelectrogen bacterial community via functional layers for microbial fuel cell applications - Iannaci, Alessandro; Myles, Adam; Flinois, Thomas; Behan A., James; Barrière, Frédéric; Scanlan, Eoin; Colavita, Paula (My University, 2020)
Grafting of aryldiazonium cations bearing a p-mannoside functionality over microbial fuel cell (MFC) anode materials was performed to investigate the ability of aryl-glycoside layers to regulate colonisation by biocatalytic biofilms. Covalent attachment was achieved via spontaneous reactions and via electrochemically-assisted grafting using potential step experiments. The effect of different functionalisation protocols on MFC performance is discussed in terms of changes in wettability, roughness and electrochemical response of modified electrodes. Water contact angle measurements (WCA) show that aryl-mannoside grafting yields a significant increase in hydrophilic character. Surface roughness determinations via atomic force microscopy (AFM) suggest a more disordered glycan adlayer when electrografting is used to facilitate chemisorption. MFCs were used as living sensors to successfully test the coated electrodes: the response of the MFCs in terms of start-up time was accelerated when compared to that of MFC equipped with non-modified electrodes, this suggests a faster development of a mature biofilm community resulting from aryldiazonium modifications, as confirmed by cyclic voltammetry of MFC anodes. These results therefore indicate that modification with glycans offers a bioinspired route to accelerating biofilm colonisation without any adverse effects on final MFC outputs.
PUBLISHED
Keywords: Exoelectrogen biofilms; Aryl-mannoside layers; Microbial fuel cell; Glycan adlayers